In Vivo18F‐APN‐1607 Tau Positron Emission Tomography Imaging in MAPT Mutations: Cross‐Sectional and Longitudinal Findings. Issue 3 (29th November 2021) - Zhou, Xin‐Yue; Lu, Jia‐Ying; Liu, Feng‐Tao; Wu, Ping; Zhao, Jue; Ju, Zi‐Zhao; Tang, Yi‐Lin; Shi, Qing‐Yi; Lin, Hua‐Mei; Wu, Jian‐Jun; Yen, Tzu‐Chen; Zuo, Chuan‐Tao; et al.
ABSTRACT: Background: Frontotemporal lobar degeneration with tauopathy caused by MAPT ( microtubule‐associated protein tau ) mutations is a highly heterogenous disorder. The ability to visualize and longitudinally monitor tau deposits may be beneficial to understand disease pathophysiology and predict clinical trajectories. Objective: The aim of this study was to investigate the cross‐sectional and longitudinal 18 F‐APN‐1607 positron emission tomography/computed tomography (PET/CT) imaging findings in MAPT mutation carriers. Methods: Seven carriers of MAPT mutations (six within exon 10 and one outside of exon 10) and 15 healthy control subjects were included. All participants underwent 18 F‐APN‐1607 PET/CT at baseline. Three carriers of exon 10 mutations received follow‐up 18 F‐APN‐1607 PET/CT scans. Standardized uptake value ratio (SUVR) maps were obtained using the cerebellar gray matter as the reference region. SUVR values observed in MAPT mutation carriers were normalized to data from healthy control subjects. A regional SUVR z score ≥ 2 was used as the criterion to define positive 18 F‐APN‐1607 PET/CT findings. Results: Although the seven study patients had heterogenous clinical phenotypes, all showed a significant 18 F‐APN‐1607 uptake characterized by high‐contrast signals. However, the anatomical localization of tau deposits differed in patients with distinct clinical symptoms. Follow‐up imaging data, which were available for three patients, demonstrated worsening trends in patterns of tau accumulation over time, which were paralleled by a significant clinical deterioration. Conclusions: Our data represent a promising step in understanding the usefulness of 18 F‐APN‐1607 PET/CT imaging for detecting tau accumulation in MAPT mutation carriers. Our preliminary follow‐up data also suggest the potential value of 18 F‐APN‐1607 PET/CT for monitoring the longitudinal trajectories of frontotemporal lobar degeneration caused by MAPT mutations. © 2021 International Parkinson and Movement Disorder Society